2013
DOI: 10.1038/modpathol.2012.203
|View full text |Cite
|
Sign up to set email alerts
|

MED12 mutations in leiomyosarcoma and extrauterine leiomyoma

Abstract: Leiomyoma and leiomyosarcoma share morphological features and smooth muscle differentiation, and both arise most frequently within the uterine corpus of middle-aged women. However, they are considered biologically unrelated tumors due to their disparate clinical, cytogenetic, and molecular features. MED12, the mediator complex subunit 12 gene, has been recently implicated as an oncogene in as many as 70% of sporadic uterine leiomyoma. In the present study, we show MED12 hotspot exon 2 mutations in extrauterine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 27 publications
5
84
2
Order By: Relevance
“…34 Sequencing of exon 2 of the MED12 gene, where the most frequently mutated codon 44 is located, revealed mutations in 47% of cases in the leiomyoma group in our study. This is in concordance with the literature reporting MED12 mutations in frequencies between 48 and 92%.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…34 Sequencing of exon 2 of the MED12 gene, where the most frequently mutated codon 44 is located, revealed mutations in 47% of cases in the leiomyoma group in our study. This is in concordance with the literature reporting MED12 mutations in frequencies between 48 and 92%.…”
Section: Discussionmentioning
confidence: 46%
“…28,29 Frequent loss of heterozygosity particularly for chromosomes 10 and 13 has been described. 30,31 Recently, the first recurrent somatic mutations of the Mediator Subcomplex 12 gene (MED12) have been demonstrated in benign and malignant uterine 32,33 and extrauterine smooth muscle tumors 34 indicating that MED12 mutations have a crucial role in tumors with smooth muscle differentiation. In addition, Fumarate Hydratase (FH)-deletions and rearrangements of high motility group protein 2 (HMGA2) have been proposed as independent somatic driver mutations in leiomyoma.…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenic mutations in exon 2 of the MED12 subunit [1] represent the most common genetic anomaly in leiomyoma, occurring in 37% [30] to 85.5% [31] (mean 64%) of uterine leiomyoma (Table 1), irrespective of ethnicity [32,33]. Together with HMGA (high mobility group AT-hook) 1 and 2 alterations, they may account for 80-90% of all uterine leiomyomas.…”
Section: Med12 and Uterine Leiomyomasmentioning
confidence: 95%
“…Of note, MED12 mutational status does not correlate with protein expression in particular in uterine leiomyoma [30,40,43]. Perot et al found MED12 protein expression by immunohistochemistry (IHC) in both MED12 mutated (6/9) and MED12 wild type uterine leiomyomas [40].…”
Section: Med12 and Uterine Leiomyomasmentioning
confidence: 96%
“…Somatic mutations are present in MED12 in sporadic leiomyoma and are present in between 37% and 70% of samples analyzed (12)(13)(14), providing ample evidence to suggest a role of MED12 as a potential oncogene. Importantly, these mutations are shared by uterine leiomyoma and uterine leiomyosarcoma (14), which clinically are considered very different diseases.…”
mentioning
confidence: 99%